Developing your communication skills in social work - Beesley, Paula; Watts, Melanie; Harrison, Mary (Los Angeles : SAGE, 2018)
What is communication and why is it important? Our ability to communicate is central to everyday life and an essential skill in social work. This easy-to-read book offers a step-by-step guide to developing effective communication skills with a diverse range of service users and professionals. It is the perfect guide to help manage different communication skills in different settings, and more importantly, encourage students to continually reflect and develop these skills.
Introduction; Chapter One - Reflection and Emotional Intelligence; Chapter Two - Initial Engagement; Chapter Three - Listening; Chapter Four - Clarification; Chapter Five - Empathy; Chapter Six - Challenging Holding Sensitive Conversations; Chapter Seven - Working with Resistance; Chapter Eight - Barriers to Effective Communication; Chapter Nine - Written Communication: Case Recording, Letters, Texts, Social Media; Chapter Ten - Assessment and Report Writing: Critical Analysis; Chapter Eleven - Inter-Professional Communication; Chapter Twelve - Managing Endings; Conclusion
Includes bibliographical references (pages 177-184) and index.
Keywords: Communication in social work; Interviewing in social service; Counselor and client; Society; Communication in social work; Counselor and client; Interviewing in social service; Society